The Formal-Informal Control Nexus During COVID-19: what Drives Informal Social Control of Social Distancing Restrictions During Lockdown? - Sargeant, Elise (Crime & delinquency, 2023)
The public rely on the police to enforce the law, and the police rely on the public to report crime and assist them with their enquiries. Police action or inaction can also impact on public willingness to informally intervene in community problems. In this paper we examine the formal-informal control nexus in the context of the COVID-19 pandemic. Drawing on a survey sample of 1,595 Australians during COVID-19 lockdown restrictions, we examine the relationship between police effectiveness, collective efficacy, and public willingness to intervene when others violate lockdown restrictions. We find that perceptions of police effectiveness in handling the COVID-19 crisis has a positive impact on the public?s willingness to intervene when others violate lockdown restrictions.